Peran Strategis TPID Klungkung dalam Pengendalian Harga Pangan Pokok Daerah - Padmayoni, Krisnanda Sukma; Widanti, Ni Putu Tirka; Dewi, Nyoman Diah Utari (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the role of the Regional Inflation Control Team (Tim Pengendalian Inflasi Daerah/TPID) in Klungkung Regency in stabilizing the prices of essential commodities and controlling inflation. It also identifies the specific strategies implemented to maintain staple food price stability at the regional level. Methodology/Approach: This study adopts a qualitative descriptive approach. Data were gathered through direct observation, in-depth interviews with stakeholders, and document analysis, focusing on TPID’s activities related to inflation control and food price stabilization. Results/Findings: The findings indicate that TPID Klungkung executed eight strategic measures: (1) market operations, (2) price monitoring, (3) coordination of supply and distribution, (4) promotion of community-based planting, (5) development of regional food reserves, (6) improvement of public communication, (7) encouragement of local product consumption, and (8) logistics system enhancement. These actions have contributed significantly to maintaining price stability and protecting consumer purchasing power, especially among low-income groups. Conclusion : This study concludes that TPID Klungkung plays a critical and proactive role in controlling inflation. The integrated multi-stakeholder approach has strengthened food security and regional economic resilience. This model serves as a best practice for other regions that face similar issues. Limitations: The study was limited by varied respondent interpretations during interviews and constrained access to some key informants, potentially affecting data depth and consistency. Contribution: This study contributes to a deeper understanding of regional inflation control mechanisms and provides practical insights for policymakers and stakeholders in designing effective community-driven economic strategies.